An optimal size for rural tourism villages with agglomeration and club-good effects - Anat Tchetchik; Aliza Fleischer; Israel Finkelshtain (European Regional Science Association (ERSA), 2010)
Historically, rural areas have been the place where most of the population lived and made its living. As a result of various economic, demographic, social and cultural changes, the second half of the 20th century was characterized by structural change in many western rural regions. Within this transition the countryside evolves as a location for leisure, recreation and tourism (LRT). Today, rural LRT is a rapidly growing industry, considered as 'panacea' to the economic and social problems of many rural communities. However, being crucially dependent on the fragile rural environment, an excessive growth of the industry may results with negative externalities, which may destroy the very same amenities that attract visitors in the first place. Accordingly, many EU countries regulate and support the rural LRT since the 1990s. Focusing on the industry's popular product; rural accommodations (RA), one possible negative result at the village level occurs as the attractiveness of localities as well as agglomeration economies create incentives for more and more households to enter the industry up to a level that harms the club good amenities of the village. A sustainable development that maintains optimum density is hence required. In this pioneer study, a conceptual and empirical framework to address this issue is provided, and the density in the RA industry is analyzed. For this purpose, a regional equilibrium model, which accounts for agglomeration effects, club-good effects as well as product differentiation, was developed. The model was estimated using data on the Israeli rural accommodations market from 2000. Significant evidences for the existences of club-good and agglomeration externalities were found and quantified in the consumer preferences and the production of rural accommodations, respectively. Using simulation mechanism a justification for regulation in the RA industry at the very local level is provided and calibrated
Keywords: 330